Attracting Top Talent Among Fresh Graduates: Perspectives From Graduate Recruiters - Aesam, Nur Zahira Amani; Muhamad Tamyez, Puteri Fadzline; Tan, Joel Barniego; E. Tarusan, Mary Ann; Aliman, Nur Sofia Nabila (Journal of Human Capital Development (JHCD), 2025)
Attracting high-potential talent among fresh graduates remains a significant challenge for organizations, despite the critical role graduates play in sustaining long-term organizational growth. This study explores (1) the challenges faced by graduate recruiters in attracting top talent among fresh graduates, and (2) the strategies recruiters employ to differentiate themselves in a competitive labour market. The findings indicate that compensation packages, employer brand recognition, employee recommendations, and job stability are key factors influencing graduates’ employment decisions. Thematic analysis further reveals three dominant themes: the digital labour market, alignment with millennial expectations, and supply–demand mismatches. The study provides practical insights for organizations seeking to position their employer brand effectively in the minds of graduates when considering career opportunities. These findings are particularly relevant for talent acquisition professionals aiming to enhance graduate recruitment strategies in increasingly competitive and digitally driven employment environments.